Cytopathological Evaluation of Thyroid by Fine Needle Aspiration Cytology and Correlation with T3 T4 and TSH Levels - Poudel, Suman; Regmi, Sudeep; Shahi, Anita; Samdurkar, Ashok (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Fine Needle Aspiration Cytology (FNAC) of the thyroid gland is now a well-established, first line diagnostic test for the evaluation of thyroid lesions. An FNA is performed along with Thyroid Function Test (TFT) profile to correlate cytology with hormonal function in symptomatic or asymptomatic patients. MATERIALAND METHODS: Total of 117 cases of FNAC of thyroid lesions were selected who had undergone TFT profile. The lesions were evaluated cytologically and categorized according to Bethesda System of classification and correlated with TFT profile. RESULTS: Out of 117 cases studied, the middle aged (20-49 years) females were most commonly affected by thyroid diseases. The predominant lesions cytologically were Benign Follicular Nodule (BFN) with frequency of 51.3%.With respect to hormonal status most of the lesions were Euthyroid (53.8%). The study showed no significant difference in mean of TFT profile with regard to various FNAC diagnoses. CONCLUSION: The study showed that FNAC and TFT profile both are essential for the proper management of thyroid lesions and, there is no significant difference between FNAC diagnosis and mean TFT profile.